Dual block HER2 assessment increased HER2 immunohistochemistry positive rate in resected specimens of gastric cancer: a prospective multicenter clinical trial from China - Chen Xu; Miaomiao Sun; Mei Jin; Zengshan Li; Rong Qin; Guoping Ren; Wenyong Sun; Lirong Chen; Lijuan Luan; Yalan Liu; Dongxian Jiang; Lingli Chen; et al. (BMC, 2022)
Abstract Background Former single center studies indicated that HER2 assessment with two primary tumor blocks (dual block HER2 assessment) could be an efficient and practical approach to overcome the adverse impact of heterogeneity and acquire a HER2 positive rate in gastric cancer (GC). This multicenter prospective clinical trial (NCT 02843412) was launched to verify its value and generality. Methods A total of 3806 participants with primary GCs have been enrolled from 8 hospitals in China. Two primary tumor blocks were selected and recorded as block 1 and block 2 after histological evaluation. An HER2 (4B5) rabbit monoclonal antibody was used for the immunohistochemistry (IHC) analysis. Results In total patients, HER2 IHC positive (3+) rate with dual block assessment (9.4%) was higher than that with single block assessment (block 1: 7.8%, block 2: 7.8%) (P < 0.001). Compared with single-block assessment, dual-block assessment increased the positive rate by approximate 20%. Similarly, HER2 equivocal (2+) rate was increased in dual block assessment (25.8%), which was higher than that in single block assessment (block 1: 20.3%, block 2: 20.9%) (P < 0.001). Conversely, dual block assessment demonstrated a lower HER2 negative (0/1+) rate (64.8%) than single block assessment (block1: 71.9%, block 2: 71.3%) (P < 0.001). These findings were also confirmed in individual hospitals. Conclusions Dual block HER2 assessment effectively increased HER2 IHC positive rate in resected specimens of GC. We recommended dual block HER2 assessment be promoted in routine clinical practice in GC. Trial registration ClinicalTrials.gov, NCT 02843412 . Registered 1 July 2016 - Retrospectively registered.